MRQ 74 & MRQ 76 extracts induce apoptosis and cell cycle arrest in colon cancer cells - Ridzwan, Norhaslinda; Rohin, Mohd A. K.; Hadi, Norhayati A.; Bakar, Mohd F. A.; Saad, Norazalina; Ishak, Ruziana (Faculty of Pharmacy, University of Benin, 2025)
MRQ 74 and MRQ 76 varieties are local fragrant rice characterized by their pleasant aroma. Keeping given phytochemicals content, these varieties have shown potency as anti-cancer agents for alternative therapies. Thus, this study aimed to elucidate cell apoptosis and cell cycle arrest in human adenocarcinoma colon cancer cells by MRQ 74 and MRQ 76 extract varieties. Methods performed include MTT assay, morphology observation, Annexin V-FITC apoptosis, and cell cycle assays. Data showed that MRQ 74 extract gives the lowest IC50 values at 24 h (0.13 ± 0.02) and 48 h (0.03 ± 0.01). While MRQ 76 extract gives the lowest IC50 value at 72 h (0.27 ± 0.01). Cell morphology observation of treated HT-29 cells showed anti-proliferation morphology following incubation with MRQ 74 and MRQ 76 extracts at their respective IC50 value for 72 h. For Annexin V-FITC assay, MRQ 76 of 3P (17.09 ± 5.38) and 3UP (24.91± 0.65) extracts showed the highest percentage of apoptotic cells at 24 h. While MRQ 74 of 3UP (34.06 ± 23.22) and FUP (54.20 ± 0.78) extracts showed the highest percentage of apoptotic cells at 48 h. In cell cycle analysis, each treatment had significantly increased percentages of the S phase from 24 h to 48 h, revealing that cell cycle arrest was induced at the S phase. In conclusion, this is the first report on the potency of MRQ 74 and MRQ 76 extracts as anti-proliferative agents by inducing apoptosis and cell cycle arrest of colon cancer cells.